Production of branched tetraethers in the marine realm: Svalbard fjord sediments revisited - Dearing Crampton-Flood, Emily; Peterse, Francien; Sinninghe Damsté, Jaap S. (2019)
Branched glycerol dialkyl glycerol tetraethers (brGDGTs) are bacterial membrane lipids thought to be predominantly produced on land. They are used as a terrestrial paleothermometer based on an empirical relation between their molecular composition and air temperature in surface soils worldwide. The proxy has been applied in continental margin sediments based on the assumption that all brGDGTs originate from land and are transported to marine sediments predominantly by rivers. However, this assumption has been challenged by the discovery of in situ brGDGT production in the coastal marine environment. To better understand marine brGDGT production, we examined newly collected marine surface sediments from the Krossfjorden and Kongsfjorden in Svalbard with a chromatography method to separate previously co-eluting 5- and 6-methylated brGDGT isomers. ‘Living’ intact polar lipid (IPL)-derived and ‘fossil’ core lipid (CL) brGDGTs were also studied for a subset of fjord sediments. The relative proportion of cyclopentane moieties in tetramethylated brGDGTs, used as indicator for brGDGT production in coastal marine settings, is much higher in the fjord sediments (#ringstetra = 0.65–0.93 for CL and 0.24–0.79 for IPL-derived brGDGTs) compared to those in nearby soils (#ringstetra = 0.00–0.37), and confirms the predominantly marine source of the brGDGTs in the fjord. Surprisingly, however, IPL-derived brGDGTs have a substantially lower #ringstetra (up to 0.52 offset) compared to that of CL-brGDGTs in the same sediment. This suggests that brGDGTs are produced in situ in different distributions throughout the year, of which the CL distribution in the sediment is an integrated signal. The offset in #ringstetra between IPL-derived and CL brGDGTs varies between 0.15 and 0.52 and increases towards the open ocean, possibly linking brGDGT production to the natural salinity gradient and associated microbial community changes.